DIGITAL LEADERSHIP ON INDIVIDUAL PERFORMANCE: A META ANALYSIS - Tulung Trilke Erita; Lengkong Victor; Nelwan Olivia; Trang Irvan; Sendow Greis (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the era of digital transformation, the capability of digital leadership has become increasingly crucial for organizational success. This study explores the impact of digital leadership on individual performance through a meta-analysis. Based on the analysis of 19 studies, digital leadership consistently shows a positive relationship with individual performance across various countries and industrial sectors. Digital leadership is seen to create a more collaborative and adaptive work environment, ultimately positively affecting individual performance. This research strengthens existing literature and provides new insights into the effectiveness of digital leadership in modern organizational contexts